Exploring Students’ Autonomous Learning Behaviours Toward E-Learning to Higher Education Performance - A Ramli Rasjid; Ahmad Al Yakin; Muthmainnah Muthmainnah; Ahmed J Obaid (STAI Hubbulwathan Duri, 2023)
There has been a recent increase in the adoption of e-learning platforms as a means of teaching in the digital age. Although many studies highlight the advantages of e-learning, there is still an urgent concern to explain why some students are unhappy with the time they spend online learning and not much is known about how students feel about it. The aim of this research is to explore how the behavior and attitudes of educators and students related to e-learning after the covid19 era. This research uses mix method with samples taken randomly from 80 faculty teacher training students. The research instrument is in the form of separate observations and surveys about their perspectives. Statistical studies show that undergraduate students have attitudes that strongly support the potential of e-learning as a pedagogical aid to support their independence in learning. The use of e-learning is felt to be able to increase independence in learning and spur students to interact with technology as a practical learning tool. Undergraduate students' perceptions of the effectiveness of e-learning can be supported by several factors, such as clear instructions, creative and innovative teachers, adequate infrastructure, and independent learning. The results of this study provide recommendations for improving teaching materials and learning models designed for blended classrooms.